Regional financing for research and development expenditure - Hervé Devillé (Brussels Studies)
Following the loss of competitiveness of most European countries with respect to the other major economic powers since the 1970s, as part of its “Europe 2020” programme, the European Union has set the objective to allocate 3% of the GDP to research and development (R&D). As part of its national reform programme, Belgium decided to follow this objective. This analysis attempts to highlight this effort at the level of the Belgian federated entities according to forecast hypotheses for GDP, R&D expenditure and its distribution between the private and public sector for 2020. With respect to the hypotheses considered, the Brussels Region would only achieve 1.9% of the GDP by this time, mainly due to a lack of private R&D expenditure in the regional territory. The Flemish Region would basically reach the objective in 2020 and the Walloon Region would exceed it thanks to a significant increase in private expenditure. At national level, Belgium would reach the objective in 2020 overall, thanks to compensations, in particular in terms of private expenditure, between the Walloon and Brussels regions